Assessing the Impact of Vehicle-to-Vehicle Communication on Lane Change Safety in Work Zones - Mariam Nour; Mohamed H. Zaki; Mohamed Abdel-Aty (IEEE Open Journal of Intelligent Transportation Systems)
Connected and automated vehicle (CAV) technology has the potential to enhance lane change safety in work zones, especially during lane closures. However, the safety implications of vehicle-to-vehicle (V2V) communication under realistic operating conditions remain insufficiently understood. This study investigates the impact of V2V communication on lane change safety in work zone scenarios using a calibrated co-simulation framework that integrates both traffic and communication networks. The framework simulates a range of realistic conditions—including varying market penetration rates (MPRs), communication ranges, and merge strategies (early and late)—and evaluates lane change safety using the time-to-collision (TTC) metric. A data dissemination algorithm is incorporated to coordinate V2V messaging and enable CAVs to initiate safe lane changes. Unlike prior studies that assume ideal communication conditions, this work simulates realistic V2V communication by incorporating metrics such as packet loss and packet delivery ratio to examine their impact on lane change safety. Findings indicate that higher MPRs and extended communication ranges generally enhance safety; however, limitations in communication quality can significantly reduce these benefits—particularly in late merge scenarios, where degraded data exchange decreases safety. Sensitivity analyses further reveal that lane-change timing and communication range are critical factors influencing safety outcomes, emphasizing the need to account for communication reliability when designing and evaluating CAV-based safety interventions.